Om behovet av ett avrinningsområdesanpassat skogsbruk - Pettersson, Robin (SLU/School for Forest Management, 2011)
The Swedish forest have about 100 000 km of watercourses and it’s an important structure in Swedish landscapes and catchments. In some of the watercourses lives spieces like the freshwater pearl mussel (Margaritifera margaritifera) and brown trout (Salmo trutta) which both are sensitive for inteference from the forestry. The new EU water framework directive has a goal that all surface water will have high or good ecological- and good chemical status at latest by the 22nd December of 2015. The study has been made in the catchment of Håltjärnsbäcken and it is from a national perspective one of the most valuable streams in Sweden and which also have been included in a LIFE-project. The catchment is situated within the Eco-park of Malingsbo-Kloten and managed by Sveaskog AB. Based on how Sveas-kog AB has classified their forests, relevant environmental quality targets and current forest policies, this study concerns how forestry can work from a more catchment oriented perspective in favour to support viable populations of species like the freshwater pearl mussel and brown trout. In the work with the catchment of Håltjärnsbäcken has purpose, except to describe the watershed and the potential that exist for the management of forestry which has been to find out: 1. How much dead wood is present in Håltjärnsbäcken. 2. Find out about the existence of dead wood varies in Håltjärnsbäcken de-pending on where in the catchment is located, that is, seek out where there is any difference between streamclass 1, 2 and 3 in the precense of dead wood in water and on dry land in the riparian zone, and on the basis of this information to find out where it might be time to possibly increase the amount of dead wood in Håltjärnsbäcken. 3. Study if it´s any connection between the presence of dead wood, and wa-tercourse depths. In the sample locals quantified dead wood in the riparian zones, age structure and tree species composition in a 30 meters wide zone on the both sides on each water route. The results of Håltjärnsbäckens water catchment area showed clearly that there is a general lack of deciduous forest when comparing with FSC-standard. Further-more, it proved that there were differences in dead wood on land and in water between the different streamclasses. Most of dead wood was found in streamclass 3. One reason could be that the beaver has been active there before. The study also found that the certification standard for FSC and PEFC need clearer guidelines and recommendations for water consideration in the forest landscape. It emerged in the study an idea to introduce water-adapted forest plan ahead. It can in turn mean that the landowner gets a certification-label which confirms that the forest is managed on a sustainable manner and the forest gets a higher value on the market. 2 Håltjärnsbäcken is an interesting and easily accessible area that could be used more in continuing education for already professionals and students in planning issues and practical forest managements issues until the various types of aquatic environments.